2021
DOI: 10.1097/md.0000000000027541
|View full text |Cite
|
Sign up to set email alerts
|

Association between breakfast consumption frequency and the risk of irritable bowel syndrome among Chinese female college students

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder that affects specific groups of people. The relationship between breakfast consumption frequency and the risk of IBS is unclear. This study aimed to investigate the association between breakfast consumption frequency and the risk of IBS among Chinese female college students.In this cross-sectional study (n = 706) conducted in October 2018, the frequency of breakfast consumption was categorized as 0 to 3 times/week, 4 to 6 times/wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, the data indicated that psychosocial and sensory factors contributed to self-reported pain in IBS ( 29 ). In addition, dietary and lifestyle habits are of importance for symptom development ( 30 ). Collectively, the included studies support the importance of performing scientific studies in subjects from the general population, and not only in subjects from tertiary healthcare centers ( 4 ), where selected patients are referred who may suffer from enteric dysmotility and not by IBS, which can obscure the results ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the data indicated that psychosocial and sensory factors contributed to self-reported pain in IBS ( 29 ). In addition, dietary and lifestyle habits are of importance for symptom development ( 30 ). Collectively, the included studies support the importance of performing scientific studies in subjects from the general population, and not only in subjects from tertiary healthcare centers ( 4 ), where selected patients are referred who may suffer from enteric dysmotility and not by IBS, which can obscure the results ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders are becoming a major health problem worldwide, 1 with negative consequences on the functioning of the neurocognitive system and psychomotor performance. 2 Sleep is one of the basic biological needs of a human being, 3 and adequate sleep is responsible for maintaining the body's homeostasis and it also has a regenerative function.…”
Section: Introductionmentioning
confidence: 99%
“…Crude (PRc) and adjusted (PRadj) prevalence ratios and 95% confidence intervals (95%CIs) of the association between short sleep duration and skipping meals.Notes: a Hirshkowitz, et al (2015) 1. Model adjusted for age group, socioeconomic class, living situation, field of study, sedentary behavior, smoking and alcohol consumption; 2 Model adjusted for sex, age group, socioeconomic class, time of day attending university, weight status, sedentary behavior and smoking; 3 Model adjusted for sex, age group, socioeconomic class, sedentary behavior and smoking.…”
mentioning
confidence: 99%
“…higher breakfast frequency has long been recognized as a healthy dietary pattern [9].The positive association between breakfast consumption and nutrition level [10], .Recent research has shown an association between regular consumption of breakfast and Coronary Heart Disease [11], Depression [12],obesity [13] [14].However, most college students do not realize the importance of breakfast. A cross-sectional study on Chinese college students shows that 27.5% of college students skip breakfast [15]。Another study on Chinese female college students found that 12.3% of female college students had breakfast less than three times a week [16]。Previous researches showed that dietary habits may increase the risk of skeletal muscle pain by having a hold on the nutrition intake of human body [17] [18].However,to date, studies regarding the negative effect of certain eating habits on skeletal muscle pain have primarily focused on simply investigating the association between diet selection and the risk of skeletal muscle pain; few studies on the association between breakfast frequency and skeletal muscle pain have been reported at this stage, and based on previous studies that found the association between breakfast frequency and nutritional level, chronic diseases, we speculated that there might be some association between breakfast frequency and skeletal muscle pain.Therefore, we designed a cohort study aiming to investigate the relationship between the breakfast frequency and the skeletal muscle pain in Chinese college students.…”
Section: Introductionmentioning
confidence: 99%